EU-funded initiatives for real world evidence: descriptive analysis of their characteristics and relevance for regulatory decision-making. Issue 6 (14th June 2018) - Plueschke, Kelly; McGettigan, Patricia; Pacurariu, Alexandra; Kurz, Xavier; Cave, Alison
Abstract : Introduction: A review of European Union (EU)-funded initiatives linked to 'Real World Evidence' (RWE) was performed to determine whether their outputs could be used for the generation of real-world data able to support the European Medicines Agency (EMA)'s regulatory decision-making on medicines. Method: The initiatives were identified from publicly available websites. Their topics were categorised into five areas: 'Data source', 'Methodology', 'Governance model', 'Analytical model' and 'Infrastructure'. To assess their immediate relevance for medicines evaluation, their therapeutic areas were compared with the products recommended for EU approval in 2016 and those included in the EMA pharmaceutical business pipeline. Results: Of 171 originally identified EU-funded initiatives, 65 were selected based on their primary and secondary objectives (35 'Data source' initiatives, 15 'Methodology', 10 'Governance model', 17 'Analytical model' and 25 'Infrastructure'). These 65 initiatives received over 734 million Euros of public funding. At the time of evaluation, the published outputs of the 40 completed initiatives did not always match their original objectives. Overall, public information was limited, data access was not explicit and their sustainability was unclear. The topics matched 8 of 14 therapeutic areas of the products recommended for approval in 2016 and 8 of 15 therapeutic areas in the 2017–2019 pharmaceutical business pipeline. Haematology, gastroenterology or cardiovascular systems were poorly represented. Conclusions: This landscape of EU-funded initiatives linked to RWE which started before 31 December 2016 highlighted that the immediate utilisation of their outputs to support regulatory decision-making is limited, often due to insufficient available information and to discrepancies between outputs and objectives. Furthermore, the restricted sustainability of the initiatives impacts on their downstream utility. Multiple projects focussing on the same therapeutic areas increase the likelihood of duplication of both efforts and resources. These issues contribute to gaps in generating RWE for medicines and diminish returns on the public funds invested.